Single Electron Transistors as Position Detectors for Nano Electomechanical Systems (Bulletin of Pure and Applied Sciences – Physics, 2021)
We have studied the single electron transistors are extremely sensitive devices as position  detectors for nanoelectromechanical systems. Suspended carbon nanotubes have observed a  reduction of the mechanical resonance frequency of the fundamental bending at low bias  voltages near the degenerate region. This effect is a precursor of the mechanical instability  and thus of the current blockade. We have found that the consequence of a capacitive  electromechanical coupling in a suspended single electron transistor when the supporting  beam is brought close to the Euler buckling instability by a lateral compression force. The  result is that the low bias current blockade originating from the coupling between the  electronic degrees of freedom and the classical resonator enhanced by several orders of  magnitude in the vicinity of the instability. These results are a direct consequence of the  continuous nature of the Eular buckling instability and the associated critical slowing down  of the fundamental bending mode of the beam at the instability. Our results frequently have  close and instructive analogies with mean field theory of second order phase transitions. In  order to increase energy, we can increase the electrostating coupling between the oscillator  and the single electron transistor, since energy depends quadratically on electrostatic force  and a large change in the gate voltage is found when electrons tunnel. In the way of reducing  oscillator spring constant in a controlled manner is to operate a doubly clamped beam subject  to a lateral compression force. Under the action of the lateral compression force the system  exhibited a continuous transition from a flat to a blockade state, while the fundamental  bending mode became softer as approached the mechanical instability. We have found that  near the buckling instability the current blockade induced by the mechanical resonator is  strongly enhanced, rendering this effect. The obtained results were found in good agreement  with previously obtained results.